2006
DOI: 10.2223/jped.1527
|View full text |Cite
|
Sign up to set email alerts
|

Early microbial colonization of cystic fibrosis patients identified by neonatal screening, with emphasis on Staphylococcus aureus

Abstract: Objectives: To assess bacterial colonization prospectively in patients with cystic fibrosis identified by neonatal screening. To assess susceptibility to antimicrobials and to perform the molecular typing of Staphylococcus aureus strains isolated from the oropharynx of patients during the study.Methods: Twenty-five cystic fibrosis patients receiving regular treatment at the Cystic Fibrosis Outpatient Clinic of Hospital de Clínicas of Universidade Federal do Paraná, Brazil, were included in the study. All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Epidemiologic studies identified a strong correlation between S. aureus colonization in the upper airway and onset of VAP, and a transition from S. aureus to P. aeruginosa as the primary pathogens in early-to late-onset VAP (37,38). A similar transition is observed in cystic fibrosis patients (39)(40)(41). This sequence of infections suggests that S. aureus colonization and co-infection may promote infection by other bacterial species.…”
Section: Discussionmentioning
confidence: 81%
“…Epidemiologic studies identified a strong correlation between S. aureus colonization in the upper airway and onset of VAP, and a transition from S. aureus to P. aeruginosa as the primary pathogens in early-to late-onset VAP (37,38). A similar transition is observed in cystic fibrosis patients (39)(40)(41). This sequence of infections suggests that S. aureus colonization and co-infection may promote infection by other bacterial species.…”
Section: Discussionmentioning
confidence: 81%
“…Cross-sectional data from the international databases indicate that the airways of CF patients are colonized early in their life by S. aureus. Recently, a Brazilian study followed early microbial colonization of cystic fibrosis patients during a 17-month prospective single center study including 25 patients identified by neonatal screening (Souza et al, 2006). S. aureus was the first pathogen in 18 patients (72%), 2 patients were colonized by MRSA strains (Brazilian clone).…”
Section: Early Colonization Of the Airways By S Aureusmentioning
confidence: 99%
“…Occasionally, millimetric nodular calcifications may be appreciated [ 33 ]. Mediastinal lymphadenopathies [ 34 ] and coexisting emphysema may occur. Patients presenting with typical UIP features do not undergo lung biopsy and are diagnosed as IPF patients [ 18 ] ( Figure 3 a).…”
Section: Idiopathic Interstitial Pneumoniasmentioning
confidence: 99%